PENGARUH MANIPULASI IKLIM KANDANG MELALUI PENGKABUTAN TERHADAP RESPON FISIOLOGIS DAN KETAHANAN PANAS KAMBING SAPERA DAN PERANAKAN ETTAWA - Arif Adham Setiawan; Erwanto Erwanto; Madi Hartono; Arif Qisthon (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to determine the effect of cage microclimate manipulation with misting on physiological responses and heat resistance of goats (Sapera and Ettawa Grade). This research was conducted in April - May 2020 at Telaga Rizki People's Farm, Metro City, Lampung Province. This study used an experimental method, Split Plot design with a completely randomized design (CRD). This study used two treatments, namely modification of the pen consisting of pens without misting (K0) and pens with misting (K1) and two breed of goats, namely Sapera and Ettawa Grade (PE) goats. Each treatment was carried out 3 times. Goats as subplots and microclimate modification of the pen as the main plot. In this study, twelve female goats were used, namely 6 Sapera goats and 6 Ettawa Grade (PE) goats aged 2-3 years. The parameters observed were microclimate condition, namely air temperature, relative humidity (RH), and Temperature Humidity Index (THI), and physiological responses including rectal temperature, respiration frequency, heart rate frequency, and heat tolerance (HTC). The results of the research showed that there was significant effect (P<0.05) of treatments on RH and THI. The resilts also showed that there was no significant effect (P>0.05) of treatments on rectal temperature, heart rate, respiration frequency, HTC and environment temperature. Keywords : Misting, Pens microclimate, Physiological responses